Synthesis and evaluation of novel potent HCV NS5A inhibitors - Zhang, Hongwang (2012)
Judicious modifications to the structure of the previously reported HCV NS5A inhibitor1, resulted in more potent anti-HCV compounds with similar and in some cases improved toxicity profiles. The synthesis of nineteen new NS5A inhibitors is reported along with their ability to block HCV replication in an HCV 1b replicon system. For the most potent compounds chemical stability, stability in liver microsomes and inhibition of relevantCYP450 enzymes is also presented.